Friends like these [large type] : a novel - McCreight, Kimberly (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
Five college friends meet up in the Catskills ten years after graduation, bringing their shared past, betrayals, and secrets with them in the new novel by the New York Times bestselling author of Reconstructing Amelia.